2173. Detection of Chlamydia psittaci by rtPCR in Outbreak Specimens Tested at CDC—2018 - McGovern, Olivia L (Open Forum Infect Dis, 2019)
BACKGROUND: Psittacosis is a respiratory illness caused by Chlamydia psittaci. The most commonly available diagnostic tests are serologic tests, which have low sensitivity and can cross-react with other chlamydial species. Serologic tests also require paired sera collected weeks apart, which is impractical for patient management. Real-time polymerase chain reaction (rtPCR) testing for C. psittaci is rapid, sensitive, and specific. However, rtRCR testing is only available at the CDC Respiratory Diseases Branch laboratory, and appropriate clinical specimen types need to be validated since psittacosis case detection is infrequent. In 2018, the first large psittacosis outbreak in the United States in 30 years occurred, allowing assessment of rtPCR performance among multiple clinical specimen types. METHODS: rtPCR test positivity rate and turnaround time were determined among 89 specimens tested at CDC from 54 outbreak patients with suspected psittacosis. rtPCR testing was performed on nucleic acid extracted from clinical specimens using oligonucleotides targeting the C. psittaci locus tag CPSIT_RS01985. Clinical information was collected by patient interview and medical record review. RESULTS: Positivity rates among the most common specimen types were 4.4% (2/46) for nasopharyngeal (NP) swab, 36.4% (8/22) for sputum, and 80.0% (4/5) for stool. Of 21 (24%) specimens with available data, the average time from patient symptom onset to specimen collection was 6 days (range 1–11 days). C. psittaci was detected in specimens from 13 of 54 outbreak patients tested (Table 1); all 13 patients had radiographically-confirmed pneumonia, and 7 were rtPCR-positive from a lower respiratory specimen only. Paired sputum and NP swab specimens were tested for 6 patients; C. psittaci was detected in all sputum but only 1 NP swab. The positive NP swab was from a patient requiring intensive care unit admission and intubation. All results were reported within 1 business day of specimen receipt in the lab. CONCLUSION: These data suggest that lower respiratory specimens are more sensitive than NP swabs for rtPCR detection of C. psittaci; stool might be a suitable alternative. Widespread implementation of rtPCR testing using appropriate specimen types could improve psittacosis detection and inform timely public health interventions. [Image: see text] DISCLOSURES: All authors: No reported disclosures.